2m+8=

Simple and best practice solution for 2m+8= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+8= equation:


Simplifying
2m + 8 = 0

Reorder the terms:
8 + 2m = 0

Solving
8 + 2m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 2m = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 2m = 0 + -8
2m = 0 + -8

Combine like terms: 0 + -8 = -8
2m = -8

Divide each side by '2'.
m = -4

Simplifying
m = -4

See similar equations:

| 2x^2+15=-13x | | .07x+x=4464.2 | | -14-5y=-64 | | 5/6=5/4y | | 8t+13t=147 | | 5x=5+4(x+1) | | X^2-3x=42 | | x/12-0.4 | | x+5(100+37485738)=6x+273947 | | -7.2=57.6 | | 5(x+y)=122 | | 4+2(x+5)=10 | | x=2(x+4)-1 | | -5.5x^2+275x-1394=1906 | | 7x+8+-3x=31+5 | | ((2/7)(14x-7))=6 | | 6-5(3x+4)=-6x-11 | | 4x^25-17x=-4 | | 15-3w=-6 | | 10x-3(x+2)=1 | | 25=0.75x+10 | | -12.4=1.2s+1.8 | | 3(x-4)=(2x-3)(x-1) | | -12/23=x+9/23 | | (6y+19)(5y+7)=0 | | 26-(5/7)x=16 | | 2.7q-5.1-5.3q=3.6q-3.4 | | -18=((2/3)(6x-21)) | | 90=8x-6 | | 1+4=x-2 | | 224=3x+7(7x-20) | | -6x-5(-x-9)=40 |

Equations solver categories